Peran Mahasiswa Dalam Meningkatkan Kemampuan Membaca Al-Quran Melalui Kegiatan KKN Mengajar Mengaji - Maghribi, Amirul Maliki; Anisa, Anisa; Marsela, Anis; Syamila, Syamila; Sari, Lusi Kemala (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
Al-Qur'an Educational Park (TPQ) is an institution or community in society that organizes non-formal education in the field of Islamic religion, intending to teach Al-Qur'an reading skills to individuals starting from kindergarten age childhood to upper secondary education level. The work program KKN in Sei Gohong Village tries to increase interest in reading Al-Qur'an for students at TPQ Fathul Jannah using various methods that can be easily accepted and applied in reading the Al-Qur'an. The method for implementing this activity with a survey location and coordinating with TPQ administrator to ask about the teaching system and teaching schedule that has been set at TPQ. The amount of students at TPQ Fathul Jannah is around 47 students with 30 students Iqra level and 17 students Al-Qur'an level, and the teachers is only 1 person. Before they start reading Iqro or Al-Qur'an, they are instructed to write short surah and they try to write Arabic. The students were provided with a report card to find out the child's reading fluency. Learning to read Quran is one of the work programs KKN students in Sei Gohong Village to create children who have good morals and become the golden generation who understand religion.